Chapter 2 Learning by Design and Second Language Education - Zapata, Gabriela C. (Taylor & Francis, 2022)
"Learning by Design and Second Language Teaching establishes theoretical, research, and practice connections between the multiliteracies framework Learning by Design and L2 teaching and learning. A comprehensive introductory chapter presents the theoretical tenets of the approach and is followed by four chapters devoted to the establishment of connections between the framework and L2 instruction, information on evidence-based pedagogical practices and suggestions for their implementation, and task examples that can be adapted for use in a variety of educational contexts. Each chapter links theory and research to practical steps instructors can take to select authentic materials and create tasks in each of the framework's knowledge processes with the objective of developing L2 students' performance in the interpersonal (speaking), interpretive (reading and listening), and presentational (writing) modes of communication. A selection of guidance charts, figures, templates, and extra digital resources are included within the text to support learning and teaching. The book will be of interest to graduate students and in-service and future L2 teachers in all levels of instruction."